DINAMIKA PENGAMBILAN KEPUTUSAN PADA PERILAKU BERESIKO (KEHAMILAN TIDAK DIINGINKAN) REMAJA - Dwi Nikmah Puspitasari; Ayu Dyah Hapsari; Hetti Rahmawati; Rizky Adi Saputro (OISAA, 2022)
Unwanted pregnancies that occur outside of marriage in adolescents are problematic because they have wider after-effects academically, financially, and socially. The occurrence of unwanted pregnancy outside of marriage is certainly based on a psychological condition such as decision making at the first time an adolescent engages in risky sexual behavior. This study aims to explore cognitive considerations such as what factors are considered for risky sexual acts and also the cognitive process of risky behavior. The participants in this study were three people consisting of one male and two female who were taken by purposive sampling technique. This study used a qualitative research design with a phenomenological approach, while the data collection techniques used interviews and observations. The results of this study indicate that the factors that cause risky behavior (unwanted pregnancy) are 1) the experience of watching pornographic videos, 2) an environment that is accustomed to promiscuity, and 3) trust and comfort when interacting with partners. While systematic decision-making through several stages does not occur, because the risk behavior of individuals is more dominated by emotional states, memories of previous experiences, and the people around them, so that decision-making is more heuristic.